Humoral IgM and IgG against excretory-secretory antigens of infected murine with Schistosoma mansoni and its relationship with the cytokines Il-10 and TNF- α - Genesis Ochoa; Andrea Mujica; Emilia Barrios; Miguel Cosenza; Radhames Capellán; Jennifer Ayala; Olga Ojeda (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2015)
The diagnosis of schistosomiasis phase is complex. The murine IgM and IgG response against excretory-secretory products of Schistosoma mansoni males (PESGM), females (PESGH) and eggs (PESH), its relation to histopathology and expression of IL-10 and TNF-α was assessed by ELISA in serum of Balb / c mice with 8 and 20 weeks of infection (RI8 and RI20) and healthy mice, RS. In RI8, were observed granulomas consisting of plasma cells, macrophages and neutrophils, deposits of collagen around the granulomas and internal area of the egg. In R20SI, fibroblasts around the egg and accumulation of macrophages and plasmocito, increased collagen deposits in areas of granuloma were observed.RI8 serum IgM had a higher percentage of positivity PESGH (35%), while the highest percentage of IgG positivity was PESGH (60%) and PESH (30%). In R20SI, was 20% IgM positive and IgG against PESH PESGM 10% against and 25% positive with PESGH. No differences in IL-10 between the RS and RI8 were observed. TNF-α in RS vs RI8 and RS vs RI20 was different and statistically significant. The PESGH could detect phase acute while PESH chronic phase. The use of several antigens would be useful in the diagnosis phase.